Genetic structure of wild and farmed Nile tilapia (Oreochromis niloticus) populations in Benin based on genome wide SNP technology - Fagbemi, Mohammed NA; Pigneur, Lise-Marie; André, Adrien; Smitz, Nathalie; Gennotte, Vincent; Michaux, Johan R.; Melard, Charles; LALEYE, PHILIPPE A.; Rougeot, Carole (My University, 2021)
For the last three decades, Nile tilapia Oreochromis niloticus (Linnaeus, 1758) is considered as one of the most productive and internationally traded food fish. Although economically important, our knowledge on the genetic structure of natural and farmed populations is scarce, especially in Africa. Sustainable aquaculture however requires integrating genetic information to elaborate appropriate management practices. The aims of the present study were: (i) to characterize the genetic structure and diversity of several O. niloticus wild populations collected in four drainage basins: Mono, Niger, Ou´em´e and Volta in Benin; (ii) to compare the identified genetic profiles of these wild populations with domesticated strains bred in two Beninese fish farms and one Belgian aquaculture research center; (iii) and finally to use the data as a tool to improve management of wild genetic resources and domesticated farmed strains. In order to characterize the genetic structure of the thirteen sampled populations of O. niloticus 2.950 SNPs were used to perform a clustering analysis and investigate the genetic diversities and population differentiations. Our results showed that, populations of O. niloticus collected in different basin and farms in Benin showed low to moderate genetic differentiation (Fst from 0.018 to 0.143) with the exception of the Nangb´eto population of Mono basin, which is genetically more differentiated (Fst from 0.091 to 0.278). Compared to wild populations, there is a greater genetic proximity between the breeding populations of CRIAB and the Pendjari river population (Fst = 0.0 47), and between the Yohan-Esteve farm populations and the Gbassa population (Fst from 0.045 to 0.055). In view of the low level of inbreeding and the good growth and reproductive performance of the Togbadji population in the Mono basin, it would be a potential candidate for the development of a local strain of O. niloticus for aquaculture in Benin.
Keywords: Population genetic structure; Oreochromis niloticus; SNP; Benin